Preparation method and application of thin-layer porous carbon nitride
Patent Information
- Application Number
- CN202410896157.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-05
AI Technical Summary
但该催化剂使用了贵金属银且催化性能仍有较大提升空间
与传统方法制备的氮化碳相比,本发明制得的薄层多孔氮化碳催化剂对具有不同取代基的芳香族邻二醇C-C键具有更高的光催化断裂效率(反应速率提高约3倍),原料的转化率可达97.6%,成功解决了现有氮化碳催化剂对芳香族邻二醇C-C键光催化断裂效率低的问题,可用于高效制备芳香族醛和芳香族酸,具备较好的应用前景。
Smart Images

Figure CN118874508B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the preparation and application of a porous photocatalyst, and more particularly to a method for preparing thin-layer porous carbon nitride and its application in photocatalytic cleavage of aromatic vicinal diol C-C bonds. Background Technology
[0002] The complex molecular structure and high oxygen content of biomass make it difficult to break the C-C bonds in its molecular structure, thus hindering the preparation of high-value-added small-molecule compounds via hydrodeoxygenation. Previously, commonly used catalysts for breaking C-C bonds were primarily precious metals, which are expensive. Non-precious metal catalysts, on the other hand, have lower efficiency in breaking C-C bonds and poor reusability.
[0003] Photocatalysis is a green and sustainable technology that uses solar energy. Carbon nitride (CN), as a typical non-metallic photocatalyst, exhibits excellent stability in photocatalytic reactions and is readily available and non-toxic, making it a highly promising photocatalytic material. However, carbon nitride suffers from drawbacks such as a narrow absorption spectrum, small specific surface area, and high recombination rate of photogenerated carriers, resulting in low photocatalytic performance and low efficiency in breaking C-C bonds in aromatic vicinal diols with different substituents.
[0004] Chinese Patent 202011053924.X discloses a method for preparing a black nickel oxide catalyst and applying it to break the C-C bonds in aromatic vicinal diols. This method requires a reaction temperature of 30-190℃, a pressure of 0.1-10 MPa, and a reaction time of 2-30 h, resulting in harsh reaction conditions, high energy consumption, and a long reaction time. Chinese Patent 202110917000.8 discloses a reaction system composed of an iron catalyst, an organic base, and an organic solvent. This system can break the C-C bonds in aromatic alcohols to obtain high-value ketones and aldehydes. However, this method makes it difficult to separate the product from the organic base, and the catalyst has a low reusability rate. Reference (Green Chem., 23(24) (2021):10071-10078.) reports a method for photocatalytically breaking the C-C bonds in 1,2-diphenylethanol in an organic system using a heterojunction photocatalyst composed of carbon nitride and silver phosphate. However, this catalyst uses the precious metal silver, and its catalytic performance still has considerable room for improvement. Summary of the Invention
[0005] Purpose of the invention: The purpose of this invention is to provide a method for preparing thin-layer porous carbon nitride, solving the problem of how to prepare a carbon nitride catalyst that can efficiently break the C-C bonds in aromatic vicinal diols. Another purpose of this invention is to propose the application of this thin-layer porous carbon nitride in the photocatalytic breaking of the C-C bonds in aromatic vicinal diols, solving the problem of how to break the C-C bonds in aromatic vicinal diols with different substituents in an aqueous medium.
[0006] Technical solution: The present invention provides a method for preparing thin-layer porous carbon nitride, comprising the following steps: (1) Melamine and cyanuric acid are subjected to a hydrothermal reaction to obtain a tubular precursor; (2) The tubular precursor was stripped with an alcohol reflux solution to obtain the intermediate; (3) Calcination of the intermediate yields a thin layer of porous carbon nitride.
[0007] This invention employs a solvothermal method combining polyol intercalation and high-temperature calcination to prepare a thin-layer porous carbon nitride photocatalyst. This photocatalyst is then applied to the photocatalytic cleavage of C-C bonds in aromatic vicinal diols with different substituents in an aqueous medium, yielding high-value aromatic aldehydes and acids with excellent substrate conversion rates and high yields. In step (2), the tubular precursor is primarily stripped by the reflux of alcohols to form a thin-layer carbon nitride photocatalyst.
[0008] Preferably, in step (1), the hydrothermal reaction method is as follows: melamine and cyanuric acid are added to water and mixed, and the hydrothermal reaction is carried out at 140-180°C for 6-24 hours. After cooling, filtration, washing and drying, a tubular precursor is obtained.
[0009] Preferably, in step (1), the mass ratio of melamine to cyanuric acid is 1:1-1.5.
[0010] Preferably, in step (2), the stripping of the tubular precursor using an alcohol reflux solution includes the following steps: (21) Mix diethylene glycol and ethanol to obtain reflux liquid or use diethylene glycol alone as reflux liquid; (22) The tubular precursor is added to the reflux liquid to obtain a suspension, and the suspension is refluxed to obtain an intermediate.
[0011] Preferably, in step (21), the volume ratio of diethylene glycol to ethanol is 1:1-5.
[0012] Preferably, in step (22), the ratio of the tubular precursor to the reflux liquid is 0.4-0.8g:10-30mL, and the reflux conditions are: reflux at 80-100℃ for 1-5h.
[0013] Preferably, in step (3), the calcination method is as follows: in an inert gas atmosphere, the temperature is increased to 500-650℃ at a rate of 5-10℃ / min, and held for 3-5 hours. The inert gas can be nitrogen, argon, or other inert gases.
[0014] The present invention further applies the thin-layer porous carbon nitride prepared by the above preparation method to the photocatalytic cleavage of the C-C bonds of aromatic vicinal diols.
[0015] The thin-layer porous carbon nitride prepared by the above method exhibits excellent light absorption range, photogenerated carrier separation efficiency, and suitable band structure, which can significantly improve the efficiency of photocatalytic cleavage of C-C bonds in aromatic vicinal diols with different substituents. This application can prepare aromatic aldehydes and aromatic acids through the cleavage of C-C bonds in aromatic vicinal diols.
[0016] The above application includes the following steps:
[0017] The catalyst is a thin-layer porous carbon nitride prepared by the method according to any one of claims 1-7, wherein R1 and R2 are independently selected from substituted or unsubstituted aromatic groups, H, and substituted or unsubstituted furanyl groups, wherein R1 and R2 are not both H, and the substituent group of the aromatic group is selected from halogens or C. 1-3 Alkyl group. Halogens may be selected from F, Cl, Br, I, and R3 and R4 are independently selected from methyl or H.
[0018] Preferably, R1 is selected from phenyl, halogen or methyl-substituted phenyl, and R2 is selected from phenyl, halogen or methyl-substituted phenyl, H.
[0019] In some embodiments, compound (I) is 1,2-diphenylethylene glycol, 2,3-diphenyl-2,3-butanediol, 1,2-di-p-tolylethane-1,2-diol, 1,2-bis(4-chlorophenyl)ethane-1,2-diol, 1,2-di(furan-2-yl)ethane-1,2-diol, or 1-phenylethane-1,2-diol, with the following structural formula: , , , , , .
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: Compared with carbon nitride prepared by traditional methods, the thin-layer porous carbon nitride catalyst prepared in this invention has a higher photocatalytic breaking efficiency for the C-C bonds of aromatic vicinal diols with different substituents (the reaction rate is increased by about 3 times), and the conversion rate of raw materials can reach 97.6%. It successfully solves the problem of low photocatalytic breaking efficiency of existing carbon nitride catalysts for the C-C bonds of aromatic vicinal diols, and can be used for the efficient preparation of aromatic aldehydes and aromatic acids, with good application prospects. Attached Figure Description
[0021] Figure 1 A scanning electron microscope image of the thin-layer porous carbon nitride prepared in this invention; Figure 2XRD patterns of CN prepared by conventional methods and thin-layer porous carbon nitride prepared by the present invention; Figure 3 Fourier transform infrared spectra of CN prepared by conventional methods and thin-layer porous carbon nitride prepared by the present invention; Figure 4 Photocurrent diagrams of CN prepared by conventional methods and thin-layer porous carbon nitride prepared by the present invention; Figure 5 Impedance diagrams of CN prepared by conventional methods and thin-layer porous carbon nitride prepared by the present invention; Figure 6 Mott-Schottky diagrams of CN prepared by conventional methods and thin-layer porous carbon nitride prepared by the present invention; Figure 7 Photoluminescence spectra of CN prepared by conventional methods and thin-layer porous carbon nitride prepared by the present invention; Figure 8 The time process curve of breaking the 1,2-diphenylethylene glycol C-bond in the thin-layer porous carbon nitride prepared in Example 1 is shown. Figure 9 The graph shows the reusability of the thin-layer porous carbon nitride prepared in Example 1 by breaking the C-C bonds of 1,2-diphenylethylene glycol. Detailed Implementation
[0022] The technical solution of the present invention will be further described below with reference to the accompanying drawings.
[0023] Example 1: A method for preparing a thin-layer porous carbon nitride is as follows: Weigh 1g of melamine and 1.2g of cyanuric acid and add them to 80mL of deionized water. After stirring in an oil bath at 80℃ for 30min, pour the mixture into a stainless steel reactor lined with polytetrafluoroethylene (PTFE) for hydrothermal reaction. The hydrothermal reaction temperature is 160℃, and the holding time is 10h. The solution in the reactor is then filtered, washed, dried, and ground to obtain the tubular precursor.
[0024] Weigh 0.6 g of the tubular precursor, add 5 mL of diethylene glycol and 10 mL of ethanol to a 50 mL round-bottom flask, and reflux at 90 °C for 3 h. After cooling, centrifugation, drying, and grinding, place it in a quartz boat and heat it to 550 °C in a tube furnace under a nitrogen atmosphere at a heating rate of 10 °C / min, holding for 4 h. After cooling and grinding, a thin-layer porous carbon nitride is obtained, with the following microstructure: Figure 1 As shown.
[0025] The standard conditions for photocatalytic cleavage of the C-C bonds in aromatic vicinal diols are as follows. First, 0.01 g of the prepared carbon nitride-based photocatalyst, 0.01 g of the substrate (aromatic vicinal diol), 200 μL of acetic acid, and 2.8 mL of micellar aqueous medium (8‰ sodium dodecyl sulfonate solution) were added to a ground-glass quartz tube, which was then sealed with a rubber stopper. Next, the quartz tube was ultrasonicated for 10 min, followed by evacuation and oxygen filling using a syringe and vacuum pump. This process was repeated three times. Finally, the quartz tube was irradiated under a 300W xenon lamp for a specified time. After the reaction, 3 mL of acetonitrile and 200 μL of naphthalene solution (internal standard) were added to the quartz tube. After stirring for 5 min, the suspension was aspirated using a syringe and filtered through a 0.22 μm nylon filter membrane to obtain the analytical solution containing the substrate and product. High-performance liquid chromatography (HPLC) was used to determine the content of substrate and product in the solution to be analyzed, and the substrate conversion rate and product yield were calculated.
[0026] Under standard conditions, the thin-layer porous carbon nitride photocatalyzed the conversion of 1,2-diphenylethylene glycol to 92.1%, benzaldehyde to 43.3%, and benzoic acid to 45.2%.
[0027] Example 2: Everything else is the same as in Example 1, except that: Weigh 0.6 g of tubular precursor and 15 mL of diethylene glycol into a 50 mL round-bottom flask and reflux at 90 °C for 3 hours.
[0028] Under standard conditions, the thin-layer porous carbon nitride photocatalyst prepared in this example achieved a conversion rate of 83.2% for 1,2-diphenylethylene glycol, a yield of 53.7% for benzaldehyde, and a yield of 35.2% for benzoic acid.
[0029] Example 3: Everything else is the same as in Example 1, except that: Weigh 2g of melamine and add it to 80mL of deionized water.
[0030] Under standard conditions, the thin-layer porous carbon nitride photocatalyst prepared in this example achieved a conversion rate of 65.8% for 1,2-diphenylethylene glycol, a yield of 42.6% for benzaldehyde, and a yield of 18.7% for benzoic acid.
[0031] Example 4: A method for preparing thin-layer porous carbon nitride is as follows: 1g of melamine and 1.5g of cyanuric acid were weighed and added to 80mL of deionized water. After stirring in an oil bath at 80℃ for 30min, the mixture was poured into a stainless steel reactor lined with polytetrafluoroethylene (PTFE) for hydrothermal reaction. The hydrothermal reaction temperature was 180℃, and the holding time was 6h. The solution in the reactor was filtered, washed, dried, and ground to obtain a tubular precursor. 0.8g of the tubular precursor, 5mL of diethylene glycol, and 25mL of ethanol were weighed and added to a 50mL round-bottom flask, and refluxed at 100℃ for 3h. After cooling, centrifugation, drying, and grinding, the mixture was placed in a quartz boat and heated to 650℃ at a rate of 10℃ / min in a tube furnace under a nitrogen atmosphere, and held for 3h. After cooling and grinding, a thin-layer porous carbon nitride was obtained.
[0032] Under standard conditions, the thin-layer porous carbon nitride photocatalyst prepared in this example achieved a conversion rate of 95.6% for 2,3-diphenyl-2,3-butanediol, a yield of 51.2% for benzaldehyde, and a yield of 40.7% for benzoic acid.
[0033] Example 5: A method for preparing a thin-layer porous carbon nitride is as follows: The specific steps are as follows: Weigh 1g of melamine and 1g of cyanuric acid and add them to 80mL of deionized water. After stirring in an oil bath at 80℃ for 30min, pour the mixture into a stainless steel reactor lined with polytetrafluoroethylene (PTFE) for hydrothermal reaction. The hydrothermal reaction temperature is 140℃, and the holding time is 24h. After filtering, washing, drying, and grinding the solution in the reactor, a tubular precursor can be obtained. Weigh 0.4g of the tubular precursor, 5mL of diethylene glycol, and 5mL of ethanol and add them to a 50mL round-bottom flask. Reflux at 80℃ for 5 hours. After cooling, centrifugation, drying, and grinding, place it in a quartz boat and heat it to 500℃ at a heating rate of 5℃ / min in an argon atmosphere in a tube furnace for 5h. After cooling and grinding, a thin-layer porous carbon nitride can be obtained.
[0034] Under standard conditions, the thin-layer porous carbon nitride photocatalyst prepared in this example achieved a conversion rate of 91.8% for 1,2-bis(4-chlorophenyl)ethane-1,2-diol, a yield of 48.3% for p-chlorobenzaldehyde, and a yield of 40.2% for p-chlorobenzoic acid.
[0035] Example 6: A method for preparing a thin-layer porous carbon nitride is as follows: The specific steps are as follows: Weigh 1g of melamine and 1.4g of cyanuric acid and add them to 80mL of deionized water. After stirring in an oil bath at 80℃ for 30min, pour the mixture into a stainless steel reactor lined with polytetrafluoroethylene (PTFE) for hydrothermal reaction. The hydrothermal reaction temperature is 170℃, and the holding time is 16h. After filtering, washing, drying, and grinding the solution in the reactor, a tubular precursor can be obtained. Weigh 0.7g of the tubular precursor, 5mL of diethylene glycol, and 15mL of ethanol and add them to a 50mL round-bottom flask. Reflux at 95℃ for 4 hours. After cooling, centrifugation, drying, and grinding, place it in a quartz boat and heat it to 600℃ in a tube furnace under a helium atmosphere at a heating rate of 8℃ / min for 4h. After cooling and grinding, a thin-layer porous carbon nitride can be obtained.
[0036] Under standard conditions, the conversion rate of 1,2-di-p-tolylethane-1,2-diol obtained by the thin-layer porous carbon nitride photocatalyst in this embodiment was 87.3%, the yield of p-tolualdehyde was 42.6%, and the yield of p-toluic acid was 40.4%.
[0037] Example 7: A method for preparing a thin-layer porous carbon nitride is as follows: 1g of melamine and 1.1g of cyanuric acid were weighed and added to 80mL of deionized water. After stirring in an oil bath at 80℃ for 30min, the mixture was poured into a stainless steel reactor lined with polytetrafluoroethylene (PTFE) for hydrothermal reaction. The hydrothermal reaction temperature was 150℃, and the holding time was 12h. The solution in the reactor was filtered, washed, dried, and ground to obtain a tubular precursor. 0.5g of the tubular precursor, 10mL of diethylene glycol, and 10mL of ethanol were weighed and added to a 50mL round-bottom flask, and refluxed at 85℃ for 4h. After cooling, centrifugation, drying, and grinding, the mixture was placed in a quartz boat and heated to 550℃ at a rate of 10℃ / min in a tube furnace under a nitrogen atmosphere, and held for 5h. After cooling and grinding, a thin-layer porous carbon nitride was obtained.
[0038] Under standard conditions, the thin-layer porous carbon nitride photocatalyst prepared in this example achieved a conversion rate of 97.6% for 1,2-bis(furan-2-yl)ethane-1,2-diol, a yield of 61.3% for furan-2-carboxaldehyde, and a yield of 30.2% for furan-2-carboxylic acid.
[0039] Example 8: The preparation method of thin-layer porous carbon nitride is as follows: The specific steps are as follows: Weigh 1g of melamine and 1.5g of cyanuric acid and add them to 80mL of deionized water. After stirring in an oil bath at 80℃ for 30min, pour the mixture into a stainless steel reactor lined with polytetrafluoroethylene (PTFE) for hydrothermal reaction. The hydrothermal reaction temperature is 160℃, and the holding time is 18h. After filtering, washing, drying, and grinding the solution in the reactor, a tubular precursor can be obtained. Weigh 0.6g of the tubular precursor, 10mL of diethylene glycol, and 15mL of ethanol and add them to a 50mL round-bottom flask. Reflux at 90℃ for 2 hours. After cooling, centrifugation, drying, and grinding, place it in a quartz boat and heat it to 550℃ in a tube furnace under a nitrogen atmosphere at a heating rate of 5℃ / min for 5h. After cooling and grinding, a thin-layer porous carbon nitride can be obtained.
[0040] Under standard conditions, the thin-layer porous carbon nitride photocatalyst prepared in this example achieved a conversion rate of 67.8% for 1-phenylethane-1,2-diol, a yield of 46.3% for benzaldehyde, and a yield of 17.2% for benzoic acid.
[0041] Comparative Example 1: Carbon nitride photocatalyst was prepared as follows: 10g of melamine was weighed, ground evenly, and then added to a 50mL crucible. The crucible was placed in a muffle furnace and heated to 550℃ at a rate of 10℃ / min, and held at that temperature for 4 hours. After cooling and grinding, carbon nitride photocatalyst CN prepared by conventional methods was obtained.
[0042] Under standard conditions, the carbon nitride photocatalyst achieved a photocatalytic conversion rate of 32.4% for 1,2-diphenylethylene glycol, a yield of 21.6% for benzaldehyde, and a yield of 8.2% for benzoic acid.
[0043] The carbon nitride prepared in Example 1 and Comparative Example 1 were used as samples, and XRD, Fourier transform infrared spectroscopy, photocurrent measurement, impedance measurement, Mott-Schottky spectroscopy, and photoluminescence spectroscopy were performed respectively. The results are as follows: Figure 2-7 As shown.
[0044] Comparative Example 2: Carbon nitride photocatalyst was prepared as follows: 10g of urea was weighed, ground evenly, and then added to a 50mL crucible. The crucible was placed in a muffle furnace and heated to 550℃ at a rate of 10℃ / min, and held at that temperature for 4 hours. After cooling and grinding, a pale yellow carbon nitride photocatalyst was obtained.
[0045] Under standard conditions, the carbon nitride photocatalyst achieved a photocatalytic conversion rate of 46.3% for 1,2-diphenylethylene glycol, a yield of 31.6% for benzaldehyde, and a yield of 9.7% for benzoic acid.
[0046] Comparative Example 3: Carbon nitride photocatalyst was prepared as follows: A method for preparing carbon nitride photocatalysts with different substituents and C-bond cleavage in aromatic vicinal diols has been reported in the reference (ChemSusChem, 13(19) (2020): 5248-5255.). The specific steps are as follows: 40 g of urea was dispersed in a mixed solution of 60 mL of 0.2 mol / L HCl and 52 mL of ethanol. 32 mL of tetraethyl orthosilicate was added to the solution while continuously stirring. After stirring continuously at room temperature for 3 hours, the solvent was removed by rotary evaporation. The resulting powder was dried and ground to obtain a white solid powder. The powder was then heated to 550 °C in a tube furnace under a nitrogen atmosphere at a heating rate of 2.5 °C / min and held at that temperature for 4 hours. After cooling and grinding, carbon nitride photocatalyst was obtained.
[0047] Under standard conditions, the carbon nitride photocatalyst catalyzed a conversion rate of 78.6% for 1,2-diphenylethylene glycol, a yield of 60.3% for benzaldehyde, and a yield of 13.2% for benzoic acid.
[0048] Comparative Example 4: Everything else is the same as in Example 1, except that: Replace the mixture of 5 mL diethylene glycol and 10 mL ethanol with 15 mL of 5 M nitric acid aqueous solution.
[0049] Under standard conditions, the carbon nitride photocatalyst prepared in this example achieved a photocatalytic conversion of 1,2-diphenylethylene glycol of 34.8%, a benzaldehyde yield of 14.8%, and a benzoic acid yield of 17.1%.
[0050] This comparative example demonstrates that the choice of reflux solution is crucial to the catalytic activity of carbon nitride photocatalysts, and ordinary strong acid reflux treatment cannot obtain carbon nitride products with high catalytic activity.
[0051] Comparative Example 5: Everything else is the same as in Example 1, except that: The tubular precursor was first calcined, and then the calcined product was refluxed with 5 mL of diethylene glycol and 10 mL of ethanol. The parameters and conditions for the calcination and reflux steps were the same as in Example 1.
[0052] Under standard conditions, the carbon nitride photocatalyst prepared in this example achieved a photocatalytic conversion of 1,2-diphenylethylene glycol of 45.5%, a benzaldehyde yield of 32.8%, and a benzoic acid yield of 10.7%.
[0053] This comparative example demonstrates that only calcination following reflux and exfoliation of the tubular precursor can result in a suitable product microstructure, leading to better photocatalytic performance. Conversely, improper calcination will significantly reduce the catalyst's catalytic efficiency.
[0054] Comparative Example 6: Under standard conditions, the thin-layer porous carbon nitride prepared in Examples 1-8 was used to photocatalyze 1,2-diphenylethane and bisphenol F, respectively, and the results are as follows: Table 1. Photocatalytic conversion effect of thin-layer porous carbon nitride on 1,2-diphenylethane and bisphenol F
[0055] As can be seen from the results in Table 1, the thin-layer porous carbon nitride in this invention has high catalytic selectivity for C-C bonds in aromatic vicinal diols, but low catalytic activity for C-C bonds in 1,2-diphenylethane and bisphenol F, and cannot be used for the catalytic reaction of C-C bond breaking in these substances.
[0056] As can be seen from the comparative examples above, the method for preparing thin-layer porous carbon nitride described in this invention is significantly superior to the performance of photocatalysts prepared in reported Chinese patents and literature in catalytically cleaving C-C bonds in aromatic vicinal diols. The method for preparing thin-layer porous carbon nitride provided by this invention, when applied to the photocatalytic cleavage of C-C bonds in aromatic vicinal diols, exhibits excellent substrate catalytic activity, superior reaction efficiency and product yield, and high reusability of the thin-layer porous carbon nitride catalyst.
Claims
1. The application of a thin-layer porous carbon nitride in the photocatalytic cleavage of C-C bonds in aromatic vicinal diols, characterized in that, Includes the following steps: The catalyst is a thin-layer porous carbon nitride prepared by the following method: (1) Melamine and cyanuric acid are subjected to a hydrothermal reaction to obtain a tubular precursor; (2) The tubular precursor was stripped with an alcohol reflux solution to obtain the intermediate; (3) Calcining the intermediate yields a thin layer of porous carbon nitride; In step (2), the process of using alcohol reflux liquid to strip the tubular precursor includes the following steps: (21) Mix diethylene glycol and ethanol to obtain reflux liquid or use diethylene glycol alone as reflux liquid; (22) Add the tubular precursor to the reflux liquid to obtain a suspension, and reflux the suspension to obtain an intermediate; In step (3), the calcination method is as follows: in an inert gas atmosphere, the temperature is increased to 500-650℃ at a rate of 5-10℃ / min, and held for 3-5 hours; R1 and R2 are independently selected from substituted or unsubstituted aromatic groups, H, and substituted or unsubstituted furanyl groups, wherein R1 and R2 are not both H, and the substituent group of the aromatic group is selected from halogens or C. 1-3 Alkyl group, wherein R3 and R4 are independently selected from methyl or H.
2. The application according to claim 1, characterized in that, In step (1), the hydrothermal reaction method is as follows: melamine and cyanuric acid are added to water and mixed, and the hydrothermal reaction is carried out at 140-180℃ for 6-24h. After cooling, filtration, washing and drying, tubular precursor is obtained.
3. The application according to claim 1, characterized in that, In step (1), the mass ratio of melamine to cyanuric acid is 1:1-1.
5.
4. The application according to claim 1, characterized in that, In step (21), the volume ratio of diethylene glycol to ethanol is 1:1-5.
5. The application according to claim 1, characterized in that, In step (22), the ratio of the tubular precursor to the reflux liquid is 0.4-0.8g:10-30mL, and the reflux conditions are: reflux at 80-100℃ for 1-5h.
6. The application according to claim 1, characterized in that, R1 and R2 are independently selected from phenyl, halogen, or methyl-substituted phenyl or furanyl groups.
Citation Information
Patent Citations
A method for preparing aldehydes / ketones by C / C bond cleavage
CN113651681B
Preparation method of black nickel oxide and application of black nickel oxide in oxidation reaction for catalyzing C-C bond breakage of 1, 2-diol
CN114308041A